SISTEM PEMIDANAAN TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN ANAK DI INDONESIA - Murniyati, Ni Nyoman; Sudiarta, I Ketut (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 04, Juni 2013)
Traficking of children especially the baby is part of the criminal act whichshould be abolished. Limitations in terms of economics is a major factor of thecriminal acts of trafficking children. The practice of child trafficking is a crimethat still veiled and the process of eradication must be carried out continuously.So that no more children who are victims of trafficking. Therefore, this paper willdescribe about regarding criminal system againts the perpetrators of criminalacts of trafficking children. This paper also describe the role of the community inanticipation of rampant children trafficking.
Keywords: Regarding Criminal System, Trafficking, Children